The foundations, position, and effects of the defendant’s right to defense in Iran’s legal system - Ghalei, Ehsan Salimi; Bouzari, Sepideh; Malaekeh, Ebrahim; Khairi, Razia (Penerbit Universiti Kebangsaan Malaysia, 2024)
The right to defense is the most important right of the accused. This right has certain foundations and effects that the present study tries to address with the approach of international law. The findings of this research show that the most important principles of the defendant's right to defense in Iranian law include "the principle of innocence", "the principle of human dignity", "the principle of equality of arms" and "the principle of legality". Each of these principles in Iran's legal system has been influenced by international law and has been expressed in various legal articles. For not complying with them, there is a guarantee of criminal executions, damages or disciplinary violations. Based on these principles, in Iran's legal system, it is necessary to explain the charges to the detained accused, and from the very beginning, the detained accused has the right to have access to the file and, in cases of need, to have an interpreter, as well as to have a lawyer of his choice. Even in cases of crimes with high punishment, the judge will hire a lawyer for him, and other necessary facilities for self-defense will be provided to him, and any torture of the arrested accused to obtain proof and confession is expressly prohibited in the Iranian constitution.